Upaya Remediasi Miskonsepsi Pada Materi Sel Menggunakan Model Pembelajaran Think Talk Write - Naufal Ahmad Muzakki; Sariwulan Diana; Didik Priyandoko (Jurnal Penelitian Pendidikan IPA, 2023)
In cell material, many concepts are abstract and can cause students to experience difficulties in understanding them. Every concept in biology learning is interconnected so that every concept that is built can influence the formation of the next concept. However, often students' initial concepts are misconceptions, namely the concepts possessed by students conflict with the concepts raised by experts. A good learning experience is needed so that students can understand the concept correctly. One learning model that provides a learning experience to discover and understand concepts is the Think Talk Write learning model. The purpose of this research is to remediate misconceptions about cell material by using the Think Talk Write learning model. This study used an experimental method with the type of pre-experimental research and one-group pretest-posttest research design. The subjects in this study were students of class XI IPA at SMA Muhammadiyah 5 Rancaekek consisting of 36 students. Based on the results of data processing, it was found that misconceptions in the pretest resulted in 12.78% and in the posttest it decreased to 6.25%. So it can be concluded that the Think Talk Write learning model can reduce students' misconceptions about cell material.